Analysis of green behaviors of urban residents and its implications to planning in Puerto Princesa City - Rabang, Mary Jane M. (School of Urban and Regional Planning, University of the Philippines Diliman, 2016)
This study entitled@Analysis of Green Behaviors of Urban Residents and its Implications to Planning in Puerto Princesa City" identifies the policy gaps in facilitating green behaviors of adult urban residents in Puerto Princesa City, Philippines. Specifically, the study assesses the proportions of urban residents with green behaviors in the solid waste management, sustainable energy, water conservation, green purchasing, and green transport domains, identifies the facilitating factors and barriers to green behaviors, determines the green initiatives implemented in the city, establishes the potential contributions of stakeholders, and recommends policy options to address barriers towards green behaviors and to sustain existing green behaviors.The study confirms that adult urban residents of Puerto Princesa have adopted green behaviors already, but some green behaviors are not yet widely adopted. The proportions of those who do not practice some of the green behaviors are substantial. Primary reason for green behaviors is the financial benefit derived from it, while inadequate knowledge and lack or insufficient facilities are the significant barriers. Test of correlation indicated that socio-demographic variables have positive correlations with some green behaviors, although the correlations are mostly weak or very weak. Assessment of green initiatives in the city indicated that gaps exist. Limited reach and information covered by information dissemination activities, and inadequate provision of environment-related support services and infrastructure are the relevant gaps observed.The study shows that key institutions in the city have the mandate, interests, and capabilities except capital investment to widen the impact of green initiatives.The results of the study have implications to urban planning which may be considered when designing and implementing environment-related programs, projects and activities in the city. Future initiatives should focus on green behaviors not yet being practiced, but green behaviors already adopted should be maintained and enhanced. The study suggests policy options to address the gaps in facilitating green behaviors. Proposed policy for consideration are strengthening the information, education and communication campaign and enhancing provision of environment-related support services and infrastructure.